Top-down approach to biological therapy of Crohn's disease - Hirschmann, Simon; Neurath, Markus (Expert Opinion on Biological Therapy, 2017)
INTRODUCTION: Crohn's disease (CD) is a chronic, immune-mediated condition with a potentially disabling and destructive course. Despite growing data on when to use a therapeutic 'top-down' strategy, clinical management of this complex disorder is still challenging. Currently, the discussion of 'top-down' strategy in CD mostly includes biological therapy alone or in combination. Areas covered: This article is based on a review of existing literature regarding the use of biological therapy in a 'top-down' approach for the treatment of Crohn's disease. The authors reviewed all the major databases including MEDLINE as well as DDW and ECCO abstracts, respectively. Expert opinion: A 'top-down' therapeutic approach in Crohn's disease is strongly supported by existing data in patients with several risk factors for a severe course of disease. Moreover, there is an increasing amount of published data recommending a more individualised therapeutic strategy to identify candidates for 'top-down' treatment, based on enhanced diagnostics using biomarkers. Emerging therapeutic approaches besides existing therapy concepts using biologicals may possibly redefine the 'top-down' therapeutic strategy for Crohn's disease in the future.
EVALuna2:33823